Filozoficzne trudności teorii interesariuszy - Soin, Maciej (Annales. Etyka w Życiu Gospodarczym, 2016)
Philosophical difficulties of stakeholder theory – which plays an important role in CSR and business ethics – are connected first of all with questions of its status and justification. What sense does stakeholder theory have: descriptive, instrumental or normative? And if normative, why then should executives worry about multiple stakeholder demands? It is well known that Freeman, one of the most important authors of stakeholder theory, deliberately disregarded these problems. In philosophical questions he invoked Rorty’s pragmatism, which in his opinion effectively undermined the “positivistic” dichotomy between facts and values, science and ethics, and enabled stakeholder theory to be understood at the same time as both descriptive and normative. The article presents some difficulties connected with this view, focusing on its dubious assumptions and unfavourable consequences. To the assumptions belongs a false dilemma taken from Rorty, which states that knowledge follows either a rule of representation or a rule of solidarity. One of the unfavourable consequences is the conclusion that stakeholder theory may be true only if its followers are able to force the stakeholders to accept its truthfulness. The main thesis of the article says that, as a result of pragmatic justification, stakeholder theory became a sort of arbitrary narration, which is unable to deal with its (empirical) misuses. However, a return to a more traditional view on facts and values enables us to appreciate the descriptive advantages of the theory and to identify difficulties connected with its normative layer. From this point of view, the attempt at a pragmatic interpretation of stakeholder theory was a misunderstanding that should be withdrawn from circulation.